Pengelolaan Sarana Dan Prasarana Di Sekolah Dasar Negeri Cemara Dua Kota Surakarta - Idayati, Eni, Prof. Dr. Sutama, M. Pd, Dr.Tjipto Subandi, M.Si (2017)
This study have five aims to describes: 1) provision of facilities and infrastructure, 2) an inventory of facilities and infrastructure, 3) the use of facilities and frastructure, 4) maintenance of facilities and infrastructure, and 5) the elimination of facilities and infrastructure in Cemara Dua Elementary School Of Surakarta. This research is qualitative research with etnography design. Data was collected by observation, interview, and documentation. Data validation was done through an extension of observation, improve endurance, triangulation, peer discussions, and member check. Data analysis use Milles and Huberman analysis are data reduction, data display and verification. Results of this research there are five things about: 1) The provision of facilities and infrastructure in Cemara Dua Elementary School Of Surakarta is planned at the beginning of the new school year, based on the deliberation of school community. 2) Inventory carried out before the infrastructure used, carried out in conjunction with the provision of the identity of each facility that is by pasting the code number specific inventory according to type of facility. 3) Utilization of facilities and infrastructure for all people in schools to support learning success with the principles of responsible and useful, but can not be used optimally, 4) All school members have a duty to exercise care and maintenance of facilities and infrastructure in schools, so that all school community has a sense of responsibility and sense of belonging, and 5) Elimination of facilities and infrastructure on the basis of several considerations in an old or damaged so it can not be repaired or reused.